Common obesity risk alleles in childhood attention‐deficit/hyperactivity disorder1. Issue 4 (26th March 2013) - Albayrak, Özgür; Pütter, Carolin; Volckmar, Anna‐Lena; Cichon, Sven; Hoffmann, Per; Nöthen, Markus M.; Jöckel, Karl‐Heinz; Schreiber, Stefan; Wichmann, H‐Erich; Faraone, Stephen V.; Neale, Benjamin M.; Herpertz‐Dahlmann, Beate; et al.
Abstract Children with attention‐deficit/hyperactivity disorder (ADHD) have a higher rate of obesity than children without ADHD. Obesity risk alleles may overlap with those relevant for ADHD. We examined whether risk alleles for an increased body mass index (BMI) are associated with ADHD and related quantitative traits (inattention and hyperactivity/impulsivity). We screened 32 obesity risk alleles of single nucleotide polymorphisms (SNPs) in a genome‐wide association study (GWAS) for ADHD based on 495 patients and 1, 300 population‐based controls and performed in silico analyses of the SNPs in an ADHD meta‐analysis comprising 2, 064 trios, 896 independent cases, and 2, 455 controls. In the German sample rs206936 in the NUDT3 gene (nudix; nucleoside diphosphate linked moiety X‐type motif 3) was associated with ADHD risk (OR: 1.39; P = 3.4 × 10−4; Pcorr = 0.01). In the meta‐analysis data we found rs6497416 in the intronic region of the GPRC5B gene (G protein‐coupled receptor, family C, group 5, member B; P = 7.2 × 10−4; Pcorr = 0.02) as a risk allele for ADHD. GPRC5B belongs to the metabotropic glutamate receptor family, which has been implicated in the etiology of ADHD. In the German sample rs206936 (NUDT3) and rs10938397 in the glucosamine‐6‐phosphate deaminase 2 gene (GNPDA2) were associated with inattention, whereas markers in the mitogen‐activated protein kinase 5 gene (MAP2K5) and in the cell adhesion molecule 2 gene (CADM2) were associated with hyperactivity. In the meta‐analysis data, MAP2K5 was associated with inattention, GPRC5B with hyperactivity/impulsivity and inattention and CADM2 with hyperactivity/impulsivity. Our results justify further research on the elucidation of the common genetic background of ADHD and obesity. © 2013 Wiley Periodicals, Inc.